Affective politics of Australian development volunteering. Issue 3 (21st March 2022) - Schech, Susanne
Abstract: It is widely acknowledged that emotions play an important role in international development volunteering (IDV), but researchers are divided about how they matter. For some, Northern volunteering in the Global South is an expression of political agency and solidarity with distant strangers, while for others, it is a product of neoliberal techniques of government that mobilise emotions, labour and social practices of care without challenging the status quo. This paper seeks to disentangle these contradictory claims by examining how participants in an IDV programme experience and articulate emotions, and the context in which they mobilise these emotions to fortify or critique dominant power relations. Drawing on recent theorising about the role of affect and emotion in society, and on interviews collected in Cambodia and Peru, I aim to show how emotions are shaped through relations with humans as well as with history, place and foreign policies. Attending to spatial and temporal context is important to understanding how and why volunteerism's affective relations can become sites for critiquing unequal relations and imagining development differently.